(untitled) (Philological Studies, 2019)
For the Macedonian verbs ending with the suffix –os–a/–s–a (of the type вампироса) Russian parallels are prefixal-suffixal formations with the suffix –i– (of the type ожесточить) with a causative meaning, as well as their derivatives with the postfix ся– (of the type ожесточиться) with inchoative meaning. Also the inchoative semantics in the Russian language can be expressed via prefixal-suffixal formations with the suffix –e– (of the type заржаветь) (рѓоса in Macedonian). Then the correlative causative meaning is rendered via periphrastic constructions (of the type сделать (плуг) ржавым or привести к тому, что (плуг заржавел)). In the Russian language the periphrastic constructions are widely used instead of prefixal-suffixal forms with the suffixes –i– and –e–, for instance сделать (людей) жестокими instead of ожесточить, сделаться or стать жестокими instead of ожесточиться, сделаться instead of стать жестокими instead of ожесточиться, сделаться instead of заржаветь. Such periphrastic constructions can be also found in Macedonian language, although their participation in the expression of causativity and inchoativenes does not have the level of significance as it has in Russian language. Such a state reflects the relevant typological features of the two compeared languages.